Lermontovs poem «Sail» translated by Abay: the problem of adequacy (Eurasian Journal of Philology Science and Education, 2018)
The problem of adequant and equivalent translation still remains relevant. For the adoption of these concepts is paid enough attention as in theory, so practically. Taking into consideration well known ttheorist of translation we may consider that term adequancycan be interpreted as interchangeable with term equivalent, where the last is determined as adequance of translation. But another theorist of translation Komissarov defines this term in another way. According to him, adequant translation must be equated to well done translation, which provides required completeness of interlanguage communication in specific conditions. Lets consider the translation of the poem *sail* by Lermontov, translated by Kunanbaev A. Thus, AbayKunanbaevs translation responds to all requirements oa adequate translation, excepting some distinctive features of plot organization and expression plan, which can be explained by distinctive features of conventional use of words in Kazakh language, and by the willing of the translator to pragmatically adopt the original text